Bias-selected full Red/Green/Blue color sensing and imaging based on inversely stacked radial PINIP junctions. Issue 3 (27th August 2020) - Zhang, Ting; Cao, Luyao; Zhang, Shaobo; Liu, Zongguang; Wang, Junzhuan; Shi, Yi; Xu, Jun; Chen, Kunji; Yu, Linwei
Abstract: Seeking an ultra-compact new architecture or strategy to achieve filter-less Red/Green/Blue (RGB) color sensing is critical for developing a wide range of high-resolution, low-cost and flexible color discrimination and imaging applications. In this work, a new inversely stacked biomimetic radial junction (RJ) PINIP photodetector, comprising of coaxial multilayers of intrinsic and doped hydrogenated amorphous Si (a-Si:H) thin films coated over silicon nanowires (SiNWs), is demonstrated, which can accomplish bias-selected and tunable spectrum responses to the R, G and B color bands, mimicking the response mechanism in human eyes. Compared to the Bayer matrix sensors, the width of a fundamental RJ-PINIP sensing unit is reduced from ∼3 μ m to <500 nm, with an absorber i-layer thinned substantially from ∼1 μ m to only ∼50 nm, which is particularly important to achieve a faster photo response and suppress the instability issues in a-Si:H absorber. Notably, the 3D RJ-PINIP sensors can now be easily constructed upon flexible aluminum foils (AF) and operate with a convenient two-terminal connection, which is a prerequisite for scalable matrix device implementation. As a prototype demo, the RGB color sensing and reconstruction functionalities are verified in a 125-RGB color imaging with 520*700 pixels, highlighting their unique potential for developing ultra-compact and flexible RGB imaging applications.